Discusions on the orientations of technology imports in Vietnam - Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Researches of importing technology into Vietnam focus on proactive choices concerning the basic characteristics of the technology that can enter the service of different targets, with high and low levels, many channels of technology transfer, with both breadth and depth, to take steps before and after. We were interested in importing technology and issued many policies to promote technology. However, what happens in practice is far from expectations. The analyzed and proposed orientation such as importing technologies towards to serving some important task, selecting technologies suitable for immediate development stage, diversification of channels and partners in the import of technology, simultaneously, noting important channel and strategic partners, focusing on both the breadth and depth of technology transfer, a key industry pioneer in promoting technology transfer... will improve the efficiency of use of technology in our country in the coming period. Code: 16122301